Methylenetetrahydrofolate Reductase C677T Gene Polymorphism as Risk Factor for Psoriasis in Saudis. Issue 14 (February 2019) - Huraib, Ghaleb Bin; Harthi, Fahad Al; Arfin, Misbahul; Khlaiwi, Ahmad Al; Rizvi, Sadaf; Al-Asmari, Abdulrahman
Methylenetetrahydrofolate reductase (MTHFR) has been linked with the etiopathogenesis of psoriasis with inconsistent results. Methylenetetrahydrofolate reductase C677T polymorphism was evaluated in 106 Saudi psoriasis vulgaris patients and 280 matched healthy controls using PCR-RFLP (restriction fragment length plymorphism) technique. The cardiovascular risk factors were also compared in cases and controls. Allele T and genotypes CT and TT were found to be increased while allele C and genotype CC significantly decreased in psoriasis patients as compared with controls ( P < .001). These results showed that the T-allele and T-containing genotypes (TT, CT) of MTHFR C677T are significantly linked with psoriasis susceptibility while C-allele and CC genotype are protective for it. Body mass index, fasting glucose, total cholesterol, low-density lipoprotein, triglycerides, and C-reactive protein, known markers for cardiovascular diseases, were found to be significantly elevated in the patient group as compared with the controls. It is concluded that the MTHFR C677T polymorphism increases psoriasis risk in Saudi patients.